Yield of five varieties of lucerne during four years of evaluation - Rivas Jacobo, Marco Antonio; Herrera Haro, José Guadalupe; Hernández-Garay, Alfonso; Vaquera Huerta, Humberto; Alejos De La Fuente3, José Isidro; Cadena-Villegas, Said (Revista Mexicana de Ciencias Agrícolas, 2020)
The aim of this study was characterize the forage production of five lucerne varieties in Montecillos, Texcoco, state of Mexico. Grassland with varieties Cuf-101, Moapa, Oaxaca and Valenciana were established in 2004, in which the annual dry matter yield (ADMY), seasonal yield (SY), forage accumulation rate (FAR) and leaf: stem ratio. The data were analyzed by the GLM procedure of SAS and comparison of means by the Tukey test. Changes by season, variety and years and their interactions were analyzed. Differences (p< 0.05) in ADMY, MSE, FAR and leaf: stem relationship were found between varieties, seasons and years. During the first year, higher ADMY was observed, and decreased to 57% at the end of the evaluation period. The Oaxaca variety maintained the highest production at the end of the evaluation and Moapa the lowest. In the SY it was observed that in summer it had the highest performance and in winter it decreased about 50%, a trend that was maintained during the evaluation period, this difference decreases over the years, with a more constant accumulation of DM in year. The leaf: stem ratio is higher in the second year where the Cuf-101 and Valenciana varieties registered the highest relationship in the winter season. In conclusion, the genotype of the lucerne variety influences the dry matter yield by season, year and production period, where the season of greatest DM production is summer.
Keywords: biomass production; forage accumulation; lucerne; seasonal yield